Dynamic trend analysis of global psoriasis burden from 1990 to 2021: a study of gender, age, and regional differences based on GBD 2021 data - Xiong, Jikui; Xue, Tiankuo; Tong, Meng; Xu, Libo; Bai, Bingxue (Frontiers in Public Health, 2025)
BackgroundPsoriasis is a chronic immune-mediated skin disease associated with systemic comorbidities such as cardiovascular disease and depression. While genetic susceptibility, immune dysregulation, and environmental factors are known contributors, the precise etiology remains uncertain. This study uses data from the Global Burden of Disease (GBD 2021) database to examine global and regional trends in psoriasis incidence, prevalence, and disability-adjusted life years (DALYs), analyzing differences by gender, age, and region to guide public health planning.MethodsData from GBD 2021, covering 204 countries and regions, were used to estimate psoriasis incidence, prevalence, and DALYs through the DisMod-MR 2.1 model with Bayesian meta-regression to integrate multiple data sources. Annual average percentage change (AAPC) was calculated to analyze trends from 1990 to 2021, with future projections for the next 15 years based on a Bayesian age-period-cohort model.ResultsFrom 1990 to 2021, global psoriasis prevalence increased from 23.06 million to 42.98 million (an 86% rise), and incidence grew by 80% from 2.85 million to 5.10 million cases. Psoriasis-related DALYs rose from 2 million to 3.69 million (an 85% increase). Regions with high Socio-demographic Index (SDI) values, including Western Europe, high-income North America, and Andean Latin America, exhibited significantly higher prevalence, incidence, and DALY rates compared to low-SDI regions such as East Asia and Sub-Saharan Africa. The burden was marginally higher in males than females, with the largest disparities in middle-aged males (40–60 years). A positive correlation between SDI and psoriasis burden was observed, showing that higher socioeconomic regions bear a greater disease burden.ConclusionThe global psoriasis burden continues to increase, particularly in high-SDI regions, where aging populations and greater healthcare access coexist. Projections indicate that psoriasis burden will rise over the next 15 years, especially among male patients. Enhanced early diagnosis, personalized treatment, and management of comorbidities are essential to reduce psoriasis’s long-term health impacts and improve patient outcomes.